2017
DOI: 10.1515/hepo-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the essential oil from cone-berries of Juniperus communis L. (Cupressaceae)

Abstract: SummaryJuniperus communis L. (Cupressaceae) is a plant widely cultivated in the Northern hemisphere. Juniper berries, the fruit of Juniperus communis L. are a highly valued, essential oil-rich plant material used traditionally in folk medicine as antiseptic, diuretic, antirheumatic, anti-inflammatory, antibacterial and antifungicidal agent. This paper reviews information on extraction methods of the essential oil from the juniper berries, its chemical composition and antimicrobial as well as antioxidant proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Similar to the results of Höferl et al ( 2014 ), high levels of representatives of the monoterpene group, i.e., α-pinene (48.3%) and sabinene (8.4%), were found in juniper oil. α-Pinene/sabinene-rich EO exhibits antimicrobial properties affecting microbial growth; with increasing concentrations of oil, the duration of the lag phase of bacterial growth may elongate (Tserennadmid et al 2010 ; Majewska et al 2017 ; Salehi et al 2019 ). Tserennadmid et al ( 2010 ) also revealed changes in the maximum specific growth rate parameter of B. cereus exposed to juniper EO.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results of Höferl et al ( 2014 ), high levels of representatives of the monoterpene group, i.e., α-pinene (48.3%) and sabinene (8.4%), were found in juniper oil. α-Pinene/sabinene-rich EO exhibits antimicrobial properties affecting microbial growth; with increasing concentrations of oil, the duration of the lag phase of bacterial growth may elongate (Tserennadmid et al 2010 ; Majewska et al 2017 ; Salehi et al 2019 ). Tserennadmid et al ( 2010 ) also revealed changes in the maximum specific growth rate parameter of B. cereus exposed to juniper EO.…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans, C. glabrata, C. parapsilosis, Cryptococcus neoformans, Geotrichum candidum and Hansenula anomala (Majewska, Kozłowska, Kowalska, & Gruczy nska, 2017). The EOs of J. communis were also seen to act against Saccharomyces cerevisiae and vancomycin-resistant…”
Section: Antimicrobial Activitymentioning
confidence: 97%
“…EOs obtained from berries of J. communis were found to act against Escherichia coli , Staphylococcus aureus , and Hafnia alvei . The compounds of its oil‐terpene hydrocarbons such as myrcene, pinene, limonene, and sabinene showed vigorous antifungal activity against Candida albicans , C. glabrata , C. parapsilosis , Cryptococcus neoformans , Geotrichum candidum and Hansenula anomala (Majewska, Kozłowska, Kowalska, & Gruczyńska, 2017). The EOs of J. communis were also seen to act against Saccharomyces cerevisiae and vancomycin‐resistant Enterococci and E. coli O157: H7 at 0.1, 0.5, and 1% concentration (Schelz, Molnar, & Hohmann, 2006; Selim, 2011).…”
Section: Pharmacological Activities Of Conifers From Northwestern Himmentioning
confidence: 99%
“…Fir oil next to its expectorant and antiseptic action shows diuretic and antirheumatic action, whereas studies have confirmed that terpenes present in birch oil exhibit anti-inflammatory, anticancer, antibacterial and antiviral activity. [190][191] Juniper Juniperus communis L. α-Pinene, camphene, limonene, cadinene, terpinen-4-ol, myrcene, β-pinene, sabinene [192][193][194][195] Presented The review of literature presented in this paper presents the potential of trees and shrubs native to the temperate zone as sources of bioactive compounds.…”
Section: Chemical Defence Of Trees and Shrubsmentioning
confidence: 99%